2019
DOI: 10.18261/issn.2464-3076-2019-02-02
|View full text |Cite
|
Sign up to set email alerts
|

Møter i mørket

Abstract: At dårlig økonomi er negativt for helsa er godt dokumentert. Mange med psykisk helseproblemer opplever å ha dårlig økonomi, og sosial støtte og tilhørighet synes avgjørende for å bedre situasjonen. Gjennom et recovery-orientert prosjekt i Asker kommune er det etablert en venneklubb. Hensikten har vaert å møte utfordringer knyttet til mangel på sosiale arenaer og muligheter for deltakelse i sosiale sammenhenger. Ulike aktiviteter subsidiert med prosjektmidler er gjennomført i regi av medlemmer i venneklubben. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Social inequality in health is a rising problem at a global scale (Wilkinson and Pickett 2020) and is a significant component to include when exploring social support and mental health recovery (Saelør et al 2019). Inequalities in mortality have even been rising ever since the 1960s in Norway, a country often referred to as one of the world's most equal countries (Dahl and van der Wel 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social inequality in health is a rising problem at a global scale (Wilkinson and Pickett 2020) and is a significant component to include when exploring social support and mental health recovery (Saelør et al 2019). Inequalities in mortality have even been rising ever since the 1960s in Norway, a country often referred to as one of the world's most equal countries (Dahl and van der Wel 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a (mental) health-perspective this is an argument to work with varieties of support and features of social support in a more systematic and broad matter, so that services can integrate and be inspired by social support-orientations from different practices. This comes with the assumption that increased social support, and active social policy that facilitates social support and economic equality, are important dimensions in battling increased inequality in health and facilitate mental health recovery (Saelør et al 2019;Stoltenberg 2015) Method Colquhoun et al (2014) has defined a scoping review as 'a form of knowledge synthesis that addresses an exploratory research question, aimed at mapping key concepts, types of evidence, and gaps in research related to a defined area or field by systematically searching, selecting, and synthesizing existing knowledge ' (p. 1292). Where a strict systematic review typically focuses on well-defined questions and accurate study designs that will often be identified in advance, a scoping study tends to address broader topics that can include a greater variety of study designs (Arksey and O'Malley 2005).…”
Section: Introductionmentioning
confidence: 99%